Radionuclide therapy of bone metastases - Lass, Piotr (Contemporary Oncology/Współczesna Onkologia, 2001)
Most patients with bone metastases experience painful symptoms. Systemic radioisotope therapy is an alternative to traditional hemibody radiation in cases of multiple, diffuse metastases. Usually given as a single i.v. slow-push infusion it gives a pain relief beginning after one to three weeks, with a mean duration up to several months, depending of the kind of a radioisotope applied. This paper reviews the role of unsealed source therapy with these bone-seeking radiopharmaceuticals in palliating pain and improving quality of life. Indications, contraindications and complications of this therapy, as well as cost-benefit aspects are discussed.